Great ape thorax and shoulder configuration—An adaptation for arboreality or knuckle-walking?. Issue 125 (December 2018) - Thompson, Nathan E.; Rubinstein, Danielle; Larson, Susan G.
Abstract: Great apes exhibit a suite of morphological traits of the shoulder and upper thorax that have traditionally been linked to orthograde arborealism. Recently it has been proposed that these traits are instead adaptations for knuckle-walking, and more broadly, that knuckle-walking itself is an adaptation for shock absorption during terrestriality. Here we test several tenets of these hypotheses using kinematic and kinetic data from chimpanzees and macaques, and electromyographic data of shoulder muscle activity in chimpanzees. We collected 3D kinematic data to quantify motion of the acromion and trunk during quadrupedalism and vertical climbing in chimpanzees as well as ground reaction forces to investigate the presence and magnitude of impact transient forces during terrestrial locomotion in chimpanzees and macaques. We also investigated patterns of recruitment of select forelimb musculature (triceps brachii and serratus anterior) using previously collected data in chimpanzees to determine whether these muscles may function to absorb impact transient forces. We found that the acromion is significantly more elevated in vertical climbing than during knuckle-walking, while dorsoventral ranges and magnitudes of motion were similar between gaits. Ground reaction forces indicate that only a minority of strides in either chimpanzees or macaques have transient forces and, when present, these transient forces as well as loading rates are small. Electromyographic results show that activity of the triceps brachii may facilitate energy absorption while serratus anterior likely functions to support the trunk, as in other primates. Our data suggest there is little to no evidence supporting recent hypotheses that the African ape upper thorax and shoulder configuration is an adaptation for knuckle-walking, or more broadly, that knuckle-walking exists as an adaptation to absorb impact shock during terrestriality. We do however find some evidence that shoulder configuration allows greater scapular elevation in chimpanzees during arboreal behaviors (e.g., vertical climbing).